2021
DOI: 10.7759/cureus.16777
|View full text |Cite
|
Sign up to set email alerts
|

Disc Diffusion Testing of Azithromycin Against Clinical Isolates of Typhoidal Salmonellae: A Diagnostic Conundrum

Abstract: Introduction: Typhoid remains a major healthcare problem in low and middle-income countries. The emergence of extremely drug-resistant (XDR) typhoid strains from the Indian subcontinent has led to very limited therapeutic options. Azithromycin being the only oral option for XDR typhoid faces a threat of rapid resistance due to its overuse after the COVID-19 pandemic.Objective: To evaluate the reliability of azithromycin disc diffusion testing against clinical isolates of typhoidal salmonellae in comparison wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Disc diffusion data for azithromycin were available for 1,779 isolates. However, previous work has shown that disc diffusion method can detect azithromycin susceptible strains with 100% specificity and 100% sensitivity, but the sensitivity of detection of resistant strains is much lower [27,28]. Therefore, all isolates interpreted as resistant using disc diffusion were retested using MIC strips.…”
Section: Resultsmentioning
confidence: 99%
“…Disc diffusion data for azithromycin were available for 1,779 isolates. However, previous work has shown that disc diffusion method can detect azithromycin susceptible strains with 100% specificity and 100% sensitivity, but the sensitivity of detection of resistant strains is much lower [27,28]. Therefore, all isolates interpreted as resistant using disc diffusion were retested using MIC strips.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, a study conducted in Karachi found discordance in 10 (16.6%) out of 60 Salmonella isolates. 10 Another study conducted in India found discordance in 12 (12%) out of 100 isolates. 14 Similarly, in 2020 a study conducted in Karachi found discordance in 5 (0.23%) out of 2104 S. Typhi isolates.…”
Section: Discussionmentioning
confidence: 97%
“…Gradient strip methods, called the E-test, are preferable to the disk diffusion approach, as these methods measure MIC values and are more specific for reporting sensitivity. 19 Shoaib et al 10 indicated in a recent study from Karachi that the E-test could be a better choice than disk diffusion. In addition, few studies have reported problems with the E-test method.…”
Section: Discussionmentioning
confidence: 99%
“…9 The lack of antimicrobial stewardship with over-the-counter antibiotic availability contributes to increasing antimicrobial resistance in endemic regions. 10 As a result of widespread empiric use of AZM during the coronavirus disease 2019 pandemic, there is a growing risk of AZM resistance. 11 This misuse of antibiotics may lead to a complete lack of options for treating XDR typhoid.…”
Section: Introductionmentioning
confidence: 99%